ANALISIS GAYA BELAJAR PESERTA DIDIK KELAS 1 PADA PEMBELAJARAN BAHASA INDONESIA DI SDN SAWAH BESAR 01 - Arisia Senisti; Duwi Nuvitalia; Ervina Eka Subekti (STKIP Subang, 2024)
ABSTRACT To create a learning environment that suits students' needs, teachers need to first recognize the characteristics of each students such as learning styles. This study aims to describe the learning style categories (kinesthetic, auditorial, and visual) of first grade students of SDN Sawah Besar 01 in Indonesian language learning. The method in this study uses a qualitative descriptive that focuses on using research data collection techniques including interviews and questionnaires that distributed to students. This study describe the conditions when the research was conducted. The population of this study was 29 students, consisting of 16 male students and 13 female students. The results showed that the learning style of first grade students was dominated by a visual learning style which had a percentage of 44.8%, then 31% of students had a tendency to auditory learning styles, and there were 24.1% of students who had a tendency to kinesthetic learning styles.